Hidden Casualties: Burma, Siam (Thailand), and the Philippines in World War Two History and Film, - Derrah, Richard (Advances in Social Sciences Research Journal, 2018)
This paper examines the World War Two in Burma, Siam (Thailand), and the Philippines and the reflection of .that history within films produced during the same time period. War films were produced all three of these countries during the war period, but, in general, focus almost exclusively on American or British characters as the heroes. There is also very little content dealing with the casualties suffered by the indigenous populations of these countries during the war.